2005
DOI: 10.1055/s-2005-865640
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of New MIKC‐Type MADS‐Box Genes from the Moss Physcomitrella patens

Abstract: MADS-box genes encode for a large family of transcription-regulating proteins, which were isolated from all groups of eukaryotic organisms. The plant-specific MIKC-type MADS-box genes have been intensively analyzed for their roles in controlling developmental processes. Well-known are the MADS-box genes acting as homeotic selector genes in the differentiation of whorls of floral organs in seed plants. The MADS-box gene family has also been studied in non-flowering plants, such as lycophytes, pteridophytes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…MIKC*-type genes are not only present in higher eudicots but have also been identified in representatives of all major groups of land plants, including bryophytes, lycophytes, ferns, gymnosperms, basal angiosperms, eudicots, and monocots (Henschel et al, 2002;Kofuji et al, 2003;Riese et al, 2005;Rensing et al, 2008;Zobell et al, 2010;Gramzow et al, 2012;Kwantes et al, 2012). In ferns and seed plants, two different monophyletic lineages of MIKC*-type genes could be identified, the P-and S-clades, which are not present in bryophytes or lycophytes (Nam et al, 2004;Gramzow et al, 2012;Kwantes et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…MIKC*-type genes are not only present in higher eudicots but have also been identified in representatives of all major groups of land plants, including bryophytes, lycophytes, ferns, gymnosperms, basal angiosperms, eudicots, and monocots (Henschel et al, 2002;Kofuji et al, 2003;Riese et al, 2005;Rensing et al, 2008;Zobell et al, 2010;Gramzow et al, 2012;Kwantes et al, 2012). In ferns and seed plants, two different monophyletic lineages of MIKC*-type genes could be identified, the P-and S-clades, which are not present in bryophytes or lycophytes (Nam et al, 2004;Gramzow et al, 2012;Kwantes et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Specificity was nevertheless preserved because only MADS-box genes that belong to the MIKC* clade were isolated. In earlier research, 11 MIKC* MADS-box genes had been identified in the moss P. patens (Henschel et al 2002;Riese et al 2005;Rensing et al 2008). In this study, 16 new bryophyte homologues were cloned: 1 from the liverwort M. polymorpha (MpMADS1), 4 from the basal moss S. subsecundum (SsMADS1 through SsMADS4 [Sphagnum subsecundum MADS-box genes 1 through 4]), and 11 from a close relative of P. patens, the moss F. hygrometrica (FhMADS1 through…”
Section: Phylogeny and Expression Of Mikc* Mads-box Genes In Bryophytesmentioning
confidence: 99%
“…However, little is known about MIKC* MADS-box genes in land plants other than Arabidopsis. As many as 11 genes are present in the moss P. patens (Rensing et al 2008), though only 2 of them have been analyzed up to now (Riese et al 2005). Herein, we report on the cloning and characterization of the MIKC* MADS-box genes from three bryophyte species: the mosses F. hygrometrica and S. subsecundum and the liverwort M. polymorpha.…”
Section: Introductionmentioning
confidence: 99%
“…The MIKC* genes in moss distinguish themselves from classical type II genes because of their longer I-domain, which is encoded by four or five exons, whereas the shorter I-domain of MIKC c proteins is encoded by a single exon (Henschel et al, 2002;Riese et al, 2005). The Arabidopsis Md genes also meet these criteria (Kofuji et al, 2003), and therefore we refer to them as Arabidopsis MIKC* genes (AtMIKC*).…”
mentioning
confidence: 99%